Increased neurocardiological interplay after mindfulness meditation: a brain oscillation-based approach - Gao, Junling; Sun, Rui; Leung, Hang Kin; Roberts, Adam; Wu, Bonnie Wai Yan; Tsang, Eric W.; Tang, Andrew C. W.; Sik, Hin Hung (Frontiers in Human Neuroscience, 2023)
Introduction: Brain oscillations facilitate interaction within the brain network and between the brain and heart activities, and the alpha wave, as a prominent brain oscillation, plays a major role in these coherent activities. We hypothesize that mindfully breathing can make the brain and heart activities more coherent in terms of increased connectivity between the electroencephalogram (EEG) and electrocardiogram (ECG) signals. Methods: Eleven participants (28-52 yr) attended eight weeks of Mindfulness Based Stress Reduction (MBSR) training. EEG and ECG data of two states of mindful breathing and rest, both eye-closed, were recorded before and after the training. EEGLAB was used to analyze the alpha band (8-12Hz) power, alpha peak frequency (APF), peak power and coherence. FMRIB was used to extract the ECG data. Heart coherence (HC) and heartbeat evoked potential were calculated for further correlation analysis. Results: After 8 weeks of MBSR training, the correlation between APF and HC increased significantly in the middle frontal region and bilateral temporal regions. The correlation between alpha coherence and heart coherence had similar changes, while alpha peak power did not reflect such changes. In contrast, spectrum analysis alone did not show difference before and after MBSR training. Conclusion: Brain works in rhythmic oscillation, and this rhythmic connection becomes more coherent with cardiac activity after MBSR training. Individual APF is relatively stable and its interplay with caridiac activity may be a more sensitive index than power spectrum by monitoring the brain-heart connection. This preliminary study has important implications for the neuroscientific measurement of meditative practice.